Stigmatizing attitudes toward people living with HIV among general adult Thai population: Results from the 5thThai National Health Examination Survey (NHES) - Kriengkrai Srithanaviboonchai (2018)
© 2017 Srithanaviboonchai et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited. Background: HIV-related stigma and discrimination is a significant driver of the HIV and AIDS epidemic. UNAIDS encourages all nations to monitor progress toward elimination of this problem. This study measured the level of stigmatizing attitudes toward people living with HIV (PLHIV) among Thai adults in the general population using recommended global tools. Methods: Data from the 5th National Health Examination Survey, conducted in 2014 were used. The survey utilized six questions recommended by the Global Stigma and Discrimination Indicator Working Group and was administered to participants aged 20–59 years old. All analyses were weighted to take into account of the probability of sampling the same-age Thai population. Factors related to a discriminatory attitude according to UNAIDS, defined as agreed to at least one of the two discriminatory issues, were evaluated using Chi square tested and multivariable logistic regression. Results: Of the 10,522 respondents, the most prevalent stigmatizing attitude was anticipated stigma (76.9%), followed by perceived stigma (69.2%), fear of HIV infection (57.0%), and social judgment (38.2%). Fifty-eight point six percent had discriminatory attitudes according to the UNAIDS global indicator. Independent predictors were being female (AOR = 1.21: 95% CI 1.14–1.29), aged 20–39 (AOR = 1.19: 95% CI 1.09–1.30) or 50–59 (AOR = 1.18: 95%CI 1.12–1.26), being Muslim (AOR = 2.03: 95%CI 1.55–2.66), earning < 10,000 Baht/month (AOR = 0.93: 95%CI 0.88–0.99), and living in the Northeast (AOR = 1.67: 95%CI 1.39–2.00) or in Bangkok (AOR = 1.73: 95%CI 1.45–2.07). Conclusions: More than half of the general adult Thai population had stigmatizing attitudes toward PLHIV. The study provided valuable baseline information which could be used as comparison for follow-up surveys with other countries. Interventions to improve Thai society’s knowledge and attitudes toward HIV/AIDS are urgently needed.